Navigating Innovation in Women Entrepreneurship: The Integral Roles of Psychological Capital, Digital Literacy, and Work-Family Conflict - Jumriaty, Jumriaty; Suhandiah, Sri; Candraningrat,, Candraningrat,; Wibowo, Januar (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2024)
This study examines the impact of psychological capital and digital literacy on innovation in entrepreneurship while also considering the mediating function of work-family conflict. This study utilised a quantitative research approach and involved a sample of 240 female entrepreneurs aged 19 to 50. The researchers collected data through a questionnaire they created and evaluated it using the WarpPLS 7.0 program. The results demonstrate that psychological capital and digital literacy have a significant and beneficial influence on innovation in entrepreneurship. Furthermore, these two variables exhibit a substantial negative association with work-family conflict. Intriguingly, work-family conflict presents a significant adverse effect on innovation. Additionally, psychological capital indirectly influences innovation via work-family strife; however, this indirect effect is not observed with digital literacy. In conclusion, psychological capital and digital literacy are crucial to enhancing innovation among female entrepreneurs. However, the friction that arises from having two roles, known as work-family conflict, might hinder innovation. Therefore, it is crucial to adopt a comprehensive approach to assist female entrepreneurs in tackling these obstacles. Keywords: Women's Entrepreneurship, Psychological Capital, Digital Literacy, Work-Family Conflict, Innovation.